17beta-Hydroxysteroid dehydrogenase-3 deficiency: from pregnancy to adolescence - Bertelloni, S; Balsamo, A; Giordani, L; Fischetto, R; Russo, G; Delvecchio, M; Gennari, M; Nicoletti, A; Maggio, M C; Concolino, D; Cavallo, L; Cicognani, A; et al. (Journal of endocrinological investigation, 2009)
Aim of this study is to report on basal clinical phenotype and follow up after diagnosis, of patients with 17beta-hydroxysteroid-dehydrogenase type 3 (17beta-HSD3) deficiency in Italy. Pediatric Endocrine Departments, University Hospitals. The cases of 5 Italian subjects affected by 17beta-HSD3 deficiency are presented in this study. Laboratory and genetic assessment. Gonadectomy and female sex assignment (4 patients) or GnRH analog therapy to regress puberty and gender identity disorder (1 patient). Presentation lasted from pregnancy (pre-natal diagnosis of a 46,XY fetus with female external genitalia) to infancy (inguinal hernia containing testes/clitoromegaly) and adolescence (virilisation). All subjects but one (subject 1, Central-Northern Italy) were from small areas of Southern Italy. Endocrine data (baseline and/or stimulated testosterone/ Delta4-androstenedione ratio) were informative. Two girls were homozygous for 17beta-HSD3 gene mutations (G289S/G289S; R80W/R80W), while the others were compound heterozygous (IVS325+4 A>T/A203V; L212Q/M235V; R80W/A235E). Four patients were confirmed as females and were well-adjusted with assigned sex; gender identity disorder improved during treatment with GnRH analog in the last subject. 17betaHSD3 deficiency may present from pregnancy to puberty for different clinical issues. Albeit testosterone/Delta4-androstenedione ratio represents the most accurate endocrine marker to diagnose the disorder, hCGstimulation is mandatory in pre-puberty. Molecular analysis of 17beta-HSD3 gene should be performed to confirm the diagnosis. Temporary GnRH analog treatment may regress gender identity disorder and provide time to confirm or change the birth sex assignment. Female individuals seems to be compliant with their sex, providing that virilisation does not occur. In Italy, the disorder seems to be more prevalent in the Southern regions and shows genetic heterogeneity.